2022
DOI: 10.3390/horticulturae8010061
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Soil Characteristics and Citrus Leaf Nutrients Contents in Current Scenario of Layyah District

Abstract: Soil with low fertility is a big problem for achieving citrus productivity. In this regard, the management of macro and micronutrients is essential. Macro and micronutrient deficiency decreased the yield and the quality of citrus fruit. It is the need of the hour to classify the soil fertility status under changing climatic scenarios. The current soil fertility survey was conducted to examine the macro and micronutrient status in the citrus production area. In soil, three depths (0–15, 15–30, and 30–45 cm) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Behera et al [25] reported significant negative correlation of soil pH with available P, available Zn, available Fe, available Mn in farmland of Bhopal Madhya Pradesh. Similar results were reported in soils of Harda district of Madhya Pradesh Tagore, et al, [41] citrus orchard soil for Layahh district of Pakistan [6]. The negative relationship observed between soil pH and the availability of cationic micronutrients in our research underscores that variations in soil pH directly impact the levels of these micronutrients in the soil Shukla et al, [42] Mishra et al, [43] Lindsay [21] indicates that for every incremental increase in soil pH within the range of 4 to 9, the solubility of zinc (Zn), copper (Cu), and manganese (Mn) decreases by 100fold, while for iron (Fe), the reduction is even more significant, at 1000-fold.…”
Section: Relationships Among Soil Properties and Citrus Yieldsupporting
confidence: 88%
See 1 more Smart Citation
“…Behera et al [25] reported significant negative correlation of soil pH with available P, available Zn, available Fe, available Mn in farmland of Bhopal Madhya Pradesh. Similar results were reported in soils of Harda district of Madhya Pradesh Tagore, et al, [41] citrus orchard soil for Layahh district of Pakistan [6]. The negative relationship observed between soil pH and the availability of cationic micronutrients in our research underscores that variations in soil pH directly impact the levels of these micronutrients in the soil Shukla et al, [42] Mishra et al, [43] Lindsay [21] indicates that for every incremental increase in soil pH within the range of 4 to 9, the solubility of zinc (Zn), copper (Cu), and manganese (Mn) decreases by 100fold, while for iron (Fe), the reduction is even more significant, at 1000-fold.…”
Section: Relationships Among Soil Properties and Citrus Yieldsupporting
confidence: 88%
“…Macro and micronutrient deficiency decreased the yield and the quality of citrus fruit. It is the need of the hour to measure soil fertility status under well-established high yielding orchards in medium-black soils [6]. Low availability of both macro and micro nutrients and their inefficient management affects crop production in different parts of the world [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Citrus fruits are consumed in large quantities globally and are considered one of the main and important types of fruits, It is characterized by a great responsiveness to nutrients, so fertilization and nutrient management affects fruit productivity and quality ]2[, this makes it an important source for the transfer of pollutants resulting from the excessive use of chemicals used in fertilization and prevention or control of epidemics ]3[. A Fertile soil, rich in nutrients is one of the determinants of establishing citrus orchards, the use of environmentally friendly organic fertilizers in citrus orchards will improve production and enhance plant strength in biological resistance to biotic and abiotic stress [4]. The establishment of citrus orchards in the central and southern regions of Iraq, which is known for the low organic content as a result of rapid decomposition and oxidation due to the prevailing climatic conditions in the region and the high summer temperatures as well as the lack of vegetation cover, makes the use of organic materials an urgent necessity in the establishment of these orchards.…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, contributes to environmental conservation and sustainable land use practices. The soils in Punjab are alkaline in nature with low to medium nitrogen (N) content, medium P and medium to high in K (Ahmad et al, 2022). In the region, a healthy amount of soil organic matter (SOM) is 1.29%, whereas soils in Pakistan fall within a wide range from 0.52 to 1.38%, with most soil falling lower than 1% in SOM (Mahmood et al, 2015).…”
Section: Introductionmentioning
confidence: 99%